Biologic Therapies in Polyarticular Juvenile Idiopathic Arthritis. Comparison of Long‐Term Safety Data from the German BIKER Registry. Issue 1 (24th November 2019) - Klein, Ariane; Becker, Ingrid; Minden, Kirsten; Hospach, Anton; Schwarz, Tobias; Foeldvari, Ivan; Huegle, Boris; Borte, Michael; Weller‐Heinemann, Frank; Dressler, Frank; Kuemmerle‐Deschner, Jasmin; Oommen, Prasad Thomas; et al.
Abstract : Objective: Biologics have an important role in the treatment of juvenile idiopathic arthritis (JIA). Long‐term safety data are limited. Direct comparison of different agents regarding occurrence of adverse events (AEs), especially of rare events, requires large quantities of patient years. In this analysis, long‐term safety with regard to AE of special interest (AESI) was compared between different biologics. Methods: Patients with nonsystemic JIA were selected from the German BIKER registry. Safety assessments were based on AE reports. Number of AEs, serious AEs, and 25 predefined AESIs, including medically important infection, uveitis, inflammatory bowel disease, cytopenia, hepatic events, anaphylaxis, depression, pregnancy, malignancy, and death, were analyzed. Event rates and relative risks were calculated using AEs reported after first dose through 70 days after last dose. Results: A total of 3873 patients entered the analysis with 7467 years of exposure to biologics. The most common AESIs were uveitis (n = 231) and medically important infections (n = 101). Cytopenia and elevation of transaminases were more frequent with tocilizumab (risk ratio [RR] 8.0, 95% confidence interval [CI] 4.2‐15, and RR 4.7, 95% CI 1.8‐12.2, respectively). Anaphylactic events were associated with intravenous route of administration. In patients ever exposed to biologics, eight malignancies were reported. Six pregnancies have been documented in patients with tumor necrosis factor inhibitors. No death occurred in this patient cohort during observation. Conclusion: Surveillance of pharmacotherapy as provided by the BIKER registry is an import approach, especially for long‐term treatment of children. Overall, tolerance was acceptable. Differences between biologics were noted and should be considered in daily patient care.